2022
DOI: 10.1002/lt.26518
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term quality of life of living liver donors: A Japanese nationwide survey

Abstract: To the editor, The most important issue in living donor liver transplantation (LDLT) is the safety of the living liver donors. Besides surgical complication, the health-related quality of life (HRQOL) of living liver donors has been called into question. [1][2][3] This study aimed to evaluate the longterm HRQOL of living liver donors based on the nationwide survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Nonetheless, all of them reported no significant differences between liver function tests and liver enzymes before and after donation, except for platelet count that was consistently lower after donation. 4,5,12–14 Despite a median follow-up time of ∼6 years, the number of enrolled patients in these studies was small at start and decreases after 1 year of follow-up. A recent study from Abdel-Khalek et al followed-up more than 200 patients over a median period of 117 months (∼9.7 years) and found that liver donors had normal liver function and enzymes at the end of follow-up, yet neither had statistical significance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nonetheless, all of them reported no significant differences between liver function tests and liver enzymes before and after donation, except for platelet count that was consistently lower after donation. 4,5,12–14 Despite a median follow-up time of ∼6 years, the number of enrolled patients in these studies was small at start and decreases after 1 year of follow-up. A recent study from Abdel-Khalek et al followed-up more than 200 patients over a median period of 117 months (∼9.7 years) and found that liver donors had normal liver function and enzymes at the end of follow-up, yet neither had statistical significance.…”
Section: Discussionmentioning
confidence: 97%
“…Almost all of them agree that donors long-term QoL is as good as of the general population. 6,8,11,12 Reports documenting on donor's long-term liver function after donation are scarce, and to our knowledge, there are none past the first decade postdonation. Fewer studies have reported on laboratory results beyond the first year of postdonation.…”
Section: Discussionmentioning
confidence: 99%